A NEW MELANOGRAPHIUM WITH MONONEMATOUS CONIDIOPHORES - Mien A. Rifai (BRIN Publishing (Penerbit BRIN), 1982)
Melanographium laxum Rifai is described and illustrated, based on colonies growing on palm petioles collected in Bogor Botanic Gardens, Java. Unlike the other members of Melanographium, the present species does not form tufted or fasciculated conidiophores.